Rainfall-Induced Stability of Reinforced Slopes with Twin Parallel Tunnels: Experimental Validation and Coupled Hydro-Mechanical Analysis - Alajlan, Zaid S.; Suliman, Loujain; Al-Hashemi, Hamzah M. B.; Alatify, Ali (Civil Engineering Journal, 2026)
Climate change has increased the frequency and intensity of extreme rainfall events, which significantly threatens slope stability by elevating pore-water pressure, reducing effective stress, and weakening soil strength. This study aims to investigate the rainfall-induced hydro-mechanical response of a fill slope containing twin parallel tunnels and to evaluate the effectiveness of reinforcement measures in improving slope stability under such conditions. A combined experimental–numerical approach was adopted. First, a physical model test of twin tunnels excavated within a slope was conducted to provide validation data for the numerical model. Subsequently, a parametric numerical analysis was performed using the finite element method implemented in PLAXIS 3D to simulate the coupled hydraulic–mechanical behavior of the slope–tunnel system under varying rainfall intensities and durations. Reinforcement measures, including piles and plates, were incorporated to assess their stabilizing performance. The results show that rainfall duration has a more significant influence on slope deformation and pore-water pressure than rainfall intensity. Reinforcement measures effectively reduce deformation and enhance slope stability, although they have limited influence on the overall saturation distribution. Reinforced slopes also exhibit increased total discharge due to preferential seepage along soil–structure interfaces. The novelty of this study lies in integrating physical model validation with three-dimensional coupled hydro-mechanical numerical analysis to comprehensively evaluate deformation, pore-water pressure, and seepage behavior in reinforced tunnel–slope systems under rainfall conditions.